Disclosure de instrumentos financeiros segundo as normas internanacionais de contabilidade: evidências empíricas de empresas brasileiras - Malaquias, Rodrigo Fernandes (2008)
This research was developed with the general objective of pointing, quantitatively, the distance of the disclosure level of financial statements of Brazilian companies, about the disclosure of financial instruments, for applications disposed by the IASB (International Accounting Standards Board). It was analyzed the annual reports that these companies provided for two different capital markets: the Brazilian, with the DFP (Demonstrações Financeiras Padronizadas) and the North American, with the Form_20F. As the observation period covers the accounting years from 2002 to 2006, and the sample involves 24 nonfinancial companies, there were collected and analyzed a total of 240 reports. The measurement of the disclosure level has been possible with the content analysis of the reports, based on a tool for data collection adapted from Lopes e Rodrigues (2007), which has 45 dichotomous topics. The results show that the accounting reports of the sample of Brazilian companies are away in different points about the requirements disposed by the IASB for the disclosure of financial instruments. This difference, which is statistically significant, exists in respect of the two capital markets for which companies provide their accounting reports. The Form_20F have a smaller distance from the IASB requirements for disclosure of financial instruments than the DFP; they meet an average of 52,65% of the tool for data collection items, and the DFP serve, on average, 37.95% of it. Thus, it concludes that the disclosure practices of the annual reports provided for the Brazilian capital market are most distant by the IASB rules than the annual reports provided for the North American capital market. Example of point that the companies should to improve in its disclosure level to comply whit the IASB rules, independent of the type report, are: i) disclosure about the relevant assumptions by the measurement of financial instruments fair value; ii) disclosure about the methods used to measure the financial risks that the company is exposed; and iii) presentation of impariment losses in financial instruments. As limits, it has the exclusion of financial institutions of the sample, the analysis of companies that issue only ADR and the documental analysis conduced, because the confidence falls in the reports prepared by companies, that were not analyzed in person. The non-adoption of different weights for the creation of the disclosure index, and the use of dichotomic variables, where other scales could be used, are also factors that limit the search.